Leaf morphological plasticity of tree species from two developmental stages in Araucaria forest - Vieira, Willyam de Lima; Boeger, Maria Regina Torres; Cosmo, Nelson Luiz; Coan, Alessandra Ike [UNESP] (FapUNIFESP (SciELO), 2014)
This study compared the morphological and anatomical variations of the leaves of four shade-tolerant tree species Allophylus edulis (St.-Hil.) Radlk (Sapindaceae), Casearia sylvestris Sw. (Salicaceae), Cupania vernalis Cambess. (Sapindaceae) and Luehea divaricata Mart. (Malvaceae) from a fragment of Araucaria forest in two developmental stages. Morphological and anatomical traits, such as leaf and tissue thickness, leaf area, leaf dry mass, specific leaf area, leaf density and stomata density were measured from 30 leaves of each developmental stage. The phenotypic plasticity index was also calculated for each quantitative trait. The results showed that the four species presented higher mean values for specific leaf area and spongy/palisade parenchyma ratio at young stage, and higher mean values for stomata density, total and palisade parenchyma thickness in the adult stage. The plasticity index demonstrated that L. divricata presented highest plasticity for both the morphological and anatomical traits while A. edulis displayed the lowest plasticity index. The results of this study indicated that the leaves of these species exhibited distinct morphological traits at each stage of development to cope with acting environmental factors.
Keywords: Leaf anatomy; Leaf morphology; Ombrophyllous mist forest; Shade tolerance